Thirteen reasons why : a novel - Asher, Jay, 1975- (New York : Razorbill, 2007)
High school student Clay Jensen receives a box in the mail containing seven cassette tapes recorded by his crush, Hannah Baker, who committed suicide, and spends a bewildering and heartbreaking night crisscrossing their town, listening to Hannah's voice recounting the events leading up to her death.
Wilson's Senior High School, January 2009
Wilson's Junior High School, November 2008
School Library Journal, November 2007
Publisher's Weekly, October 2007
Kirkus Starred, September 2007
Booklist, September 2007
Keywords: Suicide -- Juvenile fiction; High schools -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Suicide -- Fiction; High schools -- Fiction; Schools -- Fiction; Interpersonal relations -- Fiction; Suicide -- Fiction; High schools -- Fiction; School stories; Interpersonal relations -- Fiction